Engaging reality: examining how mixed reality mobile apps and games facilitate sense of place development for a more engaged citizenry - Bamesberger, Carla, author; Wolfgang, David, advisor; Castillo, Daniela, committee member; Snodgrass, Jeffrey, committee member (Colorado State University. Libraries, 2020)
Growing concerns regarding declining community and civic engagement as a result of increased access to new technologies calls for research on purposeful design that could have a reverse impact. Location aware mixed reality mobile apps and games may be one such technology that, with purposeful design, have such potential. It is possible that this technology could be purposefully designed to facilitate sense of place development among users, which can lead to outcomes like engagement in one's community. According to sense of place theory, sense of place is made up of place identity, place attachment, and place dependence, which relate to how a person experiences place. To assess this possibility, twelve users of either Pokémon Go, Ingress, or iNaturalist were interviewed and their experience of place was analyzed. All of the apps required users to spend time in place in order to use them, a key part of sense of place development. The game apps encouraged exploration, spending time in place, and noticing unique place features due to using unique place features as a key game mechanic. iNaturalist similarly encouraged exploration, spending time in place, and noticing unique features (nature) due to allowing users to take geotagged photos and upload them for identification. Competitive and team-work-oriented game mechanics facilitated online and in-person social encounters, and iNaturalist's commenting function encouraged online social interactions about place. Features of these apps facilitated experiences that relate to sense of place, suggesting that future studies on the impact that these apps have on sense of place development would be worthwhile.